A more tubulocentric view of diabetic kidney disease - Zeni, Letizia (J Nephrol, 2017)
Diabetic nephropathy (DN) is a common complication of Diabetes Mellitus (DM) Types 1 and 2, and prevention of end stage renal disease (ESRD) remains a major challenge. Despite its high prevalence, the pathogenesis of DN is still controversial. Initial glomerular disease manifested by hyperfiltration and loss of glomerular size and charge permselectivity may initiate a cascade of injuries, including tubulo-interstitial disease. Clinically, ‘microalbuminuria’ is still accepted as an early biomarker of glomerular damage, despite mounting evidence that its predictive value for DN is questionable, and findings that suggest the proximal tubule is an important link in the development of DN. The concept of ‘diabetic tubulopathy’ has emerged from recent studies, and its causative role in DN is supported by clinical and experimental evidence, as well as plausible pathogenetic mechanisms. This review explores the ‘tubulocentric’ view of DN. The recent finding that inhibition of proximal tubule (PT) glucose transport (via SGLT2) is nephro-protective in diabetic patients is discussed in relation to the tubule’s potential role in DN. Studies with a tubulocentric view of DN have stimulated alternative clinical approaches to the early detection of diabetic kidney disease. There are tubular biomarkers considered as direct indicators of injury of the proximal tubule (PT), such as N-acetyl-β-D-glucosaminidase, Neutrophil Gelatinase-Associated Lipocalin and Kidney Injury Molecule-1, and other functional PT biomarkers, such as Urine free Retinol-Binding Protein 4 and Cystatin C, which reflect impaired reabsorption of filtered proteins. The clinical application of these measurements to diabetic patients will be reviewed in the context of the need for better biomarkers for early DN.